Processo administrativo tributário: decisões definitivas diante do direito fundamental de acesso à jurisdição - Nunes, Margaret da Silva Peres (2022)
The present paper pretends to analyse the Brazilian administrative procedural system, mainly regarding the great amount of litigations at administrative tax instances, which socioeconomic outcomes are worrisome. The number of pending litigations may infer, at first sight, structural problems among organs of administration, or lack of efficiency and low productivity of the instances responsible for instruction and trial of such litigations. Without disregarding that preliminary consideration, even after those litigations are solved, should not be disconsidered the possibility of demanding the Judiciary to terminate matters already solved in the administrative circuit. Thus, the Public Treasury, in case it wins the argument, will not possess the legal means to demand the payment of the credit, having to appeal to the Judiciary to fulfill its right. The passive subject, in turn, may also resort to Justice in order to postulate the annulment of any desfavorable administrative decision. The present research will diagnose that situation and, through legal arguments, inspired by other justice systems, will propose a review of the fundamental right to justice, established in the Constitution, in a way that administrative decisions, as long as constitutional and legal requirements are articulated, may be considered definitive. Thereby, it is expected to have the extra legal effect of decreasing the amount of requests, both administratively and judicially, with undeniable socioeconomic gains. Furthermore, this paper intends to provide a modest academic contribution to the elaboration of legal measures capable of applying a new model of administrative tax jurisdiction.